Linguistic Analysis of the Development of the Term “Greenwashing” Through the Prism of Variology - K. Kovács, Krisztina (Slavica, 2026)
This article examines the variability of the ecological neologism “greenwashing.” Based on an analysis of the media context and various corpus platforms, the main types of variability (graphic, morphological, and syntactic) are revealed. Semantic variability is also presented depending on the context. Particular attention is paid to the process of determinologization in the context of the mediatization of scientific knowledge.